Analisis Psikologi Sastra Tokoh Utama Pada Novel Dan Hujan Pun Berhenti Karya Farida Susanty (Jurnal Motivasi Pendidikan dan Bahasa, 2023)
The problem discussed in this study is how the personality of Leo in the novel And the Rain Stops. This study aims to determine the inner conflicts related to personality in the novel Dan Hujan Pun Henti, by Farida Susanty using a literary psychology approach. This type of research is qualitative descriptive research. The source of this research data is the utterances and words contained in the novel Dan Hujan Pun Henti, by Farida Susanty. The data collection techniques used are reading, recording and analyzing. The results of this study stated that the main character Leo in the novel "And the Rain Stopped" by Farida Susanty experienced inner conflicts related to Sigmud Freud's psychoanalysis studies, namely: id, ego and superego. The id in the main character Leo is described that Leo does not know to distinguish between good and bad and he also seems to have lost his taste. The ego in Leo attempts to suppress Leo's id to be able to overcome it. The superego depicted by Leo is related to his feelings and seeks to cultivate a moral side to himself.